Geoscience communication: a content analysis of practice in British Columbia, Canada, using science communication models - C. C. Onstad; E. van der Flier-Keller (Geoscience Communication)
Geoscience communication, an emerging discipline within the geosciences, faces a scarcity of theoretical grounding despite abundant practical perspectives. This paper addresses this gap by investigating the application of science communication models (deficit, dialogue, participatory) in geoscience communication, specifically in British Columbia, Canada. The overarching aim is to determine if the deficit-to-dialogue shift often discussed in science communication literature is reflected in geoscience communication practice. Using a content analysis approach, data were collected from publicly accessible websites to qualify and quantify how (activities) and why (objectives) geoscience communication practitioners communicate. The activities and objectives were coded based on terms associated with each model that closely aligned with those described by Metcalfe (2019a, b). Findings reveal a persistence of the deficit model in practice (76 % for objectives, 61 % for activities) with limited adoption of dialogue and participatory approaches. This suggests a discrepancy between theoretical advancements in science communication and their application in geoscience contexts. The study highlights disparities in the use of communication models across target audiences, regions, and venues. While communication with K–12 (kindergarten–grade 12) audiences (students, educators) utilizes dialogue-based approaches, participatory activities are underrepresented, particularly in regions with high population densities (e.g. Lower Mainland/Sea to Sky is 0 % participatory) and areas where geoscience intersects with public interests (e.g. northern British Columbia is 3 % participatory). By shedding light on the current landscape of geoscience communication in British Columbia, this research informs future endeavours in theory development and practice improvement within the broader field of science communication. However, it also acknowledges the need for localized studies to capture the diverse contexts of science communication practices worldwide.